Effect of dried tangerine peel extract supplementation on the growth performance and antioxidant status of broiler chicks. Issue 4 (1st October 2016) - Jiang, Xian-Ren; Zhang, Hai-Jun; Wang, Jing; Wu, Shu-Geng; Yue, Hong-Yuan; Lü, Hui-Yuan; Cui, Hu; Bontempo, Valentino; Qi, Guang-Hai
Abstract: The aim of this study was to evaluate the effects of dried tangerine peel extract (DTPE) supplementation on the growth performance and immune and antioxidant status of broiler chicks. A total of 525 day-old, male, Arbour Acres (AA) broiler chicks were fed a basal diet (CTR) either with or without 80, 160, 240 and 480 mg DTPE/kg diet. The chicks were randomly assigned into five dietary groups for a 42-day experiment. There were seven replicates per group and 15 chicks per replicate. At 42 days of age, two birds from each cage were selected for blood sampling. The dietary DTPE supplementation linearly increased the body weight and the average daily gain ( p  = .03; p  = .03) and quadratically increased the average daily feed intake ( p  = .02) during the starter period. In addition, the plasma lysozyme level in the 80 or 160 mg/kg DTPE group increased compared to the CTR group ( p  = .02 and .07, respectively). Chicks fed 80-mg/kg DTPE reduced the malondialdehyde concentration ( p  = .02) compared with birds fed the CTR diets. Moreover, the plasma glutathione peroxidase activities in the low DTPE dietary groups (80 and 160 mg/kg) were higher than in the CTR ( p  < .01) and 240 mg/kg DTPE group ( p  < .01 and p  = .02, respectively). The results of the present study indicate that dietary DTPE with low supplemental dosage (≤160 mg/kg) might positively modulate the systemic antioxidative defence property of chicks.